Chronic kidney disease-prevalence and determinants among type 2 diabetes mellitus patients attending a primary care setting in central Kerala - Soman, Sajith Kumar; Areekal, Binu; Varghese, Rosin George; John, Susan; Gopan, Radhika S.; Jacob, Quincy Mariam; Nair, Amruthaa Raman (International Journal Of Community Medicine And Public Health, 2018)
Background: Diabetes mellitus (DM) is one of the most common metabolic diseases characterized by increased blood glucose levels either due to insufficiency/absence of insulin or due to decrease in the insulin sensitivity. The prevalence of chronic kidney disease (CKD) in people with type 2 diabetes is three times higher than in non-diabetic population and majority of people developing end-stage renal diseases (ESRD) have Type 2 DM. The objectives of the study were to find out the prevalence of CKD, mean GFR and associated factors of CKD, in diabetics coming to a primary health care setting in Central Kerala. Methods: A cross-sectional study among all patients attending the NCD clinic of Health Centre, Ettumanoor with confirmed diagnosis of type 2 diabetes mellitus was done between February 2017 and April 2017. Results: The prevalence of CKD among the study population was 45.3%. The proportion of CKD was 34.9% among those with nil urinary protein, 57.1% among those with 1+ urinary protein, 88.9% for those with 2+ and 87.5% among those with 3+ urinary protein. Among those with CKD mean duration of diabetes was 121.92 months against 92.72 months among those without CKD. There was statistically significant difference between RBS values of those with CKD and without CKD (238.49 mg% versus 199.41 mg%). The proportion of CKD was found increase with duration of diabetes 5 years (31.2%), 5-10 years (47.8%), 10-15 years (52.6%) and >15 years (55%). Conclusions: The study showed high prevalence of CKD among diabetics. The duration of diabetes, urinary protein levels and RBS value were found to have strong association with CKD in diabetics.